Surgical Correction of Ectropion: Comparison Between Full Thickness Skin Grafts and Local Flaps - Kiran, Saba; Ali Khan, Faisal Akhlaq; Ali, Hyder; Kumar, Suneel; Sami, Waqas; Khursheed, Roqayyah Munawwer (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effectiveness of two reconstruction techniques, i.e., full-thickness skin graft and local flap, for patients undergoing reconstructive surgery for ectropion repair. Study Design: Prospective comparative study. Place and Duration of Study: Department of Plastic & Reconstructive Surgery, Dr Ruth K.M. Pfau Civil Hospital Karachi, from Feb to Aug 2020. Methodology: The study was conducted after acquiring approval from the Institutional Review Board of Dow University of Health Sciences. Patients advised repairing ectropion were admitted to the ward prior to a day or night of the procedure. The consultant surgeon decided on the operative management, either using a full-thickness skin graft or a local flap, depending on the type of ectropion. Results: 60 patients were recruited for the study, with 30 patients in each group. At follow-up of two weeks, one month, and three months’ skin colour match and pliability were significantly better in patients who received local flap than those treated with a full-thickness skin graft. Out of 30, 2 (6.7%) patients developed ectropion recurrence when they received full-thickness skin graft coverage, whereas ectropion recurrence was not observed in patients managed with local flap. Conclusion: Local flap appears to be more effective than full-thickness skin graft in achieving excellent aesthetic effects in patients who underwent correction of ectropion.